Launching into commercial space innovations in space travel - Pelton, Joseph N.; Marshall, Peter (Library of flight, 2015)
Launching Into Commercial Space chronicles the dawn of a fast-moving commercial space age in which initiative from the private sector is launching innovation into tomorrow. This is the story of the pioneers and private companies developing new spacecraft, planning futuristic spaceports, and seeking to offer a range of "space travel" services.